Utilization of Iraqi Metakaolin in Special Types of Concrete: A Review Based on National Researches (Journal of Engineering, 2021)
Portland cement concrete is the most commonly used construction material in the world for decades. However, the searches in concrete technology are remaining growing to meet particular properties related to its strength, durability, and sustainability issue. Thus, several types of concrete have been developed to enhance concrete performance. Most of the modern concrete types have to contain supplementary cementitious materials (SCMs) as a partial replacement of cement. These materials are either by-products of waste such as fly ash, slag, rice husk ash, and silica fume or from a geological resource like natural pozzolans and metakaolin (MK). Ideally, the utilization of SCMs will enhance the concrete performance, minimize environmental pollution and mitigate the drawbacks of cement production attributed to the highly CO2 emission. In general, MK's ultra-fineness and high pozzolanic activity are exhibited a remarkable performance of concrete in terms of strength and durability. However, the filler effect, acceleration of cement hydration, and the pozzolanic reaction with calcium hydroxide (CH) are the main factors influencing the performance of metakaolin as a cementitious material. Therefore, numerous researches have been undertaken on inclusion MK in concrete and mortar and production of (free-cement concrete) geopolymer concrete. This paper reviews some of previous native researches on effect of using Iraqi metakaolin as a pozzolanic material in different types of concrete. The standpoint of this review will guide the researchers on the importance of utilization of local MK and highlight the missing researches toward completing a comprehensive understanding of incorporation Iraqi-metakaolin in concrete technology.